2017
DOI: 10.1249/01.mss.0000517163.52613.f4
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Resistance Training in Adults with and without Spinal Cord Injuries

Abstract: International Journal of Exercise Science 10(1): 154-165, 2017The purpose of this study was to examine the effects of active lower body eccentric resistance training (ERT) in individuals with incomplete spinal cord injury (iSCI) and controls (CON). Specifically, the study was designed to determine if those with iSCI adapt similarly to ERT as CON participants as well as the overall safety and efficacy of ERT in this population. This pilot investigation involved the recruitment of persons with iSCI (n = 3) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In support of previous work, 26 data from the current study support the contention that individuals with iSCI have the capacity to improve neuromuscular function of the affected limbs similarly to unimpaired individuals. Our participants with iSCI showed similar improvements as young, healthy men who completed 35 ERT training sessions on a knee extension machine (~39%) 27 and neurologically intact men who completed 8 weeks of unilateral knee extensors (~29%) ERT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In support of previous work, 26 data from the current study support the contention that individuals with iSCI have the capacity to improve neuromuscular function of the affected limbs similarly to unimpaired individuals. Our participants with iSCI showed similar improvements as young, healthy men who completed 35 ERT training sessions on a knee extension machine (~39%) 27 and neurologically intact men who completed 8 weeks of unilateral knee extensors (~29%) ERT.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, Stone et al 26 utilized the same training ergometer in a sample of individuals with iSCI who would be described as daily ambulators (one cervical and two thoracic iSCIs). Here, improvements in eccentric strength averaged 79% following an 8-week ERT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have shown that in patients with severe COPD, 10 weeks of EET led to increases in muscle strength and hypertrophy, at progressively lower levels of perceived fatigue and dyspnea. Similar applications of EET have led to increased lower limb strength in patients with spinal cord injuries [4] and EET is as successful as traditional rehabilitation when addressing fall risks in elderly subjects [5]. The physiological adaptation stimulated by EET in clinical populations has the potential to extend to healthy subjects and in particular to competitive sport, where the continuous search for training methods to enhance performance is paramount.…”
Section: Improving Muscle Strength Using Eccentric Ergometry Trainingmentioning
confidence: 99%
“…The eccentric muscle action (generation of tension as the muscle lengthens) consumes less oxygen per unit of work, thus allowing individuals with low cardiovascular ceilings to exercise at higher volumes compared to traditional eccentric + concentric repetitions. Those with incomplete spinal cord injury (iSCI) [11][12] [13] and other neurological conditions [14] [15] have safely performed ERT in adjunct to traditional therapeutic interventions. Outcomes from these studies include improved eccentric and isometric strength, walking function, quality of life, cardiovascular fitness, and muscle volume.…”
Section: Introductionmentioning
confidence: 99%